2013
DOI: 10.1111/jog.12144
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and cytogenetic results of a large series of amniocentesis cases from Turkey: Report of 6124 cases

Abstract: In our study, abnormal MSS (and among these, abnormal triple test result) was the most frequent indication for amniocentesis. Our overall culture success rate was 98.8%. Frequency of major chromosomal abnormality was 3.2% and trisomy 21 was the most frequent abnormality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
13
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 9 publications
8
13
1
1
Order By: Relevance
“…For a better comparison with our study, we analysed the chromosomal abnormality rates of these markers in the group that had abnormal ultrasound fi ndings. Th is analysis demonstrated that the detection rates of chromosomal abnormalities in their studies increased to 12.8, 8.1, 7 and 16.7%, respectively, consistent with our fi ndings (Gaudry Ocak et al (2013) 6,124 3.6 29 56 11.5 AMA, advanced maternal age; MSS, abnormal maternal serum screening; family history, family history of chromosomal abnormality.…”
Section: Discussionsupporting
confidence: 91%
“…For a better comparison with our study, we analysed the chromosomal abnormality rates of these markers in the group that had abnormal ultrasound fi ndings. Th is analysis demonstrated that the detection rates of chromosomal abnormalities in their studies increased to 12.8, 8.1, 7 and 16.7%, respectively, consistent with our fi ndings (Gaudry Ocak et al (2013) 6,124 3.6 29 56 11.5 AMA, advanced maternal age; MSS, abnormal maternal serum screening; family history, family history of chromosomal abnormality.…”
Section: Discussionsupporting
confidence: 91%
“…Among these, 33.00% (68/206) were numerical abnormalities, 19.90% (41/206) were structural abnormalities, and 47.09% (97/206) were polymorphic variants (clinically insignificant heterochromatin area chromosomal aberrations that were not expected to have any phenotypic effects). The most frequently observed polymorphism was an increase in the heterochromatin region of chromosome 1, which was similar to the findings of Ocak et al (2014), followed by a pericentric inversion on chromosome 9.…”
Section: Resultssupporting
confidence: 79%
“…(reviewed in Leung et al ) have indicated that about 1% of all prenatal samples would have a chromosomal abnormality not detected by rapid aneuploidy tests, of which one third may have significant risk of serious phenotypic consequences. In our study, the most common change missed by Prenatal BoBs was polymorphisms of heterochromatin regions which are clinically insignificant . However, Prenatal BoBs identified three microdeletions on prenatal samples, which were missed by KT and was successful on four prenatal samples for which KT failed.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the above-mentioned advantages, five structural changes (reciprocal translocation, ring chromosomes and isodicentric chromosomes) In our study, the most common change missed by Prenatal BoBs was polymorphisms of heterochromatin regions which are clinically insignificant. 31 However, Prenatal BoBs identified three microdeletions on prenatal samples, which were missed by KT and was successful on four prenatal samples for which KT failed. In addition, low-grade mosaics 29 and polyploidy 16 cannot be identified by Prenatal BoBs.…”
Section: Discussionmentioning
confidence: 99%